Application of Computer Technology in Supply Chain Management of Electronic Logistics. Issue 2 (May 2021) - Xing, Xueshan
Abstract: The 21st century is the information age, computer technology (hereinafter referred to as CT) has been applied to many fields, especially logistics. With the rise of e-commerce, China's logistics industry has developed rapidly, which has been extended to supply chain management (hereinafter referred to as SCM). With the maturity of e-Logistics industry, e-logistics has developed to the direction of network, which also extends to the SCM. Through SCM, enterprises can better reduce the cost of supply chain, which will increase the competitiveness of enterprises. With the integration of information industry and supply chain, enterprises can guarantee information transmission, which will better realize the sharing and sharing of resources and information. Through SCM, e-logistics can provide integrated comprehensive services, which will better improve the profitability of enterprises. Therefore, CT has become an important way to enhance the core competitiveness. First of all, this paper analyzes the importance of CT to electronic logistics (hereinafter referred to as EL). Then, this paper analyzes the application of CT in SCM.